Development and validation of a Supportive Learning Environment for Expertise Development Questionnaire (SLEED-Q) - Elvira, Quincy; Beausaert, Simon; Segers, Mien; Imants, Jeroen; Dankbaar, Ben (Learning environments research, 2016)
Development of professional expertise is the process of continually transforming the repertoire of knowledge, skills and attitudes necessary to solve domain-specific problems which begins in late secondary education and continues during higher education and throughout professional life. One educational goal is to train students to think more like experts and approach the mastery of a subject as an expert would. Helping students to develop professional expertise and evaluating whether classrooms are conducive to the development of expertise is difficult and time-consuming. At present, there is no instrument that measures all the core classroom factors that influence specifically the development of professional expertise. This paper describes the development and validation of an instrument that measures the extent to which educators create a Supportive Learning Environment for Expertise Development, the SLEED-Q. A sample of 586 secondary school students (14–18 years-old) was used for validation. Both exploratory and confirmatory factor analyses were carried out. Examination of the fit indices indicated that the model seemed to fit the data well, with the goodness-of-fit coefficients being in recommended ranges. The SLEED-Q, consisting of seven factors with 30 items, the SLEED-Q has potential as an instrument for examining how conducive learning environments are to development of professional expertise in secondary school settings. The implications of the results and potential paths for future research are considered.